Analysis of goals scored in the UEFA Champions League in the period 2009/2010 - Michailidis, Y. (Serbian Journal of Sports Sciences, 2013)
The purpose of the present study was to evaluate goal scoring characteristics of the UEFA Champions League in the period 2009 - 10; the sample consisted of all the games of the organization (N = 125). The statistical analysis of the results was conducted with the use of the non-parametric chi-square test. According to the results of the present study, the short pass (10m) comprised only 8.44% of all goals. Most of the goals (41.56%) were scored with the "place" (the inner side of the foot) and shot (33.44%), while a considerable proportion of the goals were scored with the head (16.88%). In addition, most of the goals were scored inside the penalty box (73.75%) (p Keywords Soccer, goal achievement, goal evaluate